THE DEVELOPMENT OF THE PROGRAMS TO ENHANCE A CREATIVE LEADERSHIP OF SCHOOL ADMINISTRATORS IN THE SECONDARY EDUCATIONAL SERVICE AREA OFFICE KALASIN - Khampan, Pasunee; Ruangmontri, Karn (Academic Journal of Mahamakut Buddhist University Roi Et Campus, 2023)
The research aimed 1) to study the current condition, desirable condition, and the requirement to enhance the creative leadership of school administrators under Kalasin secondary educational office, and 2) to develop a program to promote the creative leadership of school administrators under Kalasin secondary educational office. The study could be divided into 2 phases as follows, the 1st phase was to study the current condition, desirable condition, and the requirement to enhance the creative leadership of 97 school administrators under Kalasin secondary educational office, chosen by stratified random sampling technique and classified by school sizes. A questionnaire was utilized as the research instrument. The 2nd phase was to develop a program to promote the creative leadership of school administrators under Kalasin secondary educational office. Best practices of 3 qualified people - obtained by a purposive sampling method -, and the program was evaluated by 5 qualified people – selected by a purposive sampling method. The research instrument consisted of interview and evaluation forms, and the suitability and probability of the promoting program of the creative leadership of school administrators. For the statistical data analysis, it comprised mean, standard deviation and Modified Priority Needs Index: PNImodifled. For the research outcomes, it could be stated that; 1. The overall current condition of the creative leadership enhancement of school administrators under Kalasin secondary educational office was at a high level. Considering each of aspects, it was found that all the aspects were at a high level, and the highest one was visionary and ability to solve problems. Furthermore, the overall desirable condition of creative leadership development of school administrators under Kalasin secondary educational office was at the highest level. Considering each of aspects, the highest ones were individual consideration, flexibility and adaptation, visionary, and creativity; whereas the ability to solve problems for the enhancement of the creative leadership of school administrators under Kalasin secondary educational office were at a high level. The requirement to enhance the creative leadership competency could be respectively sorted from most to least, including creativity, flexibility and adaptation, visionary, individual consideration, and problem-solving competence. 2. The program to enhance the creative leadership of school administrators under Kalasin secondary educational office consisted of 1) principles, 2) purposes, 3) contents, 4) activities/development method, and 5) measurement and evaluation. Contents included 5 modules, namely the 1st module was individual consideration, the 2nd module was flexibility and adaptation, the 3rd module was visionary, the 4th module was creativity, and the 5th module was problem-solving competence. The overall result of the measurement and evaluation was at the highest level of suitability and probability.